Cardiac Computed Tomography – More Than Coronary Arteries? A Clinical Update - Taron, Jana; Foldyna, Borek; Eslami, Parastou; Hoffmann, Udo; Nikolaou, Konstantin; Bamberg, Fabian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Background Rapid improvement of scanner and postprocessing technology as well as the introduction of minimally invasive procedures requiring preoperative imaging have led to the broad utilization of cardiac computed tomography (CT) beyond coronary CT angiography (CTA).Method This review article presents an overview of recent literature on cardiac CT. The goal is to summarize the current guidelines on performing cardiac CT and to list established as well as emerging techniques with a special focus on extracoronary applications.Results and Conclusion Most recent guidelines for the appropriate use of cardiac CT include the evaluation of coronary artery disease, cardiac morphology, intra- and extracardiac structures, and functional and structural assessment of the myocardium under certain conditions. Besides coronary CTA, novel applications such as the calculation of a CT-derived fractional flow reserve (CT-FFR), assessment of myocardial function and perfusion imaging, as well as pre-interventional planning in valvular heart disease or prior pulmonary vein ablation in atrial fibrillation are becoming increasingly important. Especially these extracoronary applications are of growing interest in the field of cardiac CT and are expected to be gradually implemented in the daily clinical routine.Key Points: Citation Format
Keywords: cardiac; CT-angiography; CT